Transition of care from hospital to home for older people with chronic diseases: a qualitative study of older patients' and health care providers' perspectives - Sun, Mengjie; Qian, Yumeng; Liu, Lamei; Wang, Jianan; Zhuansun, Mengyao; Xu, Tongyao; Rosa, Ronnell Dela (Frontiers in Public Health, 2023)
Background Transitional care is a critical area of care delivery for older adults with chronic illnesses and complex health conditions. Older adults have high, ongoing care needs during the transition from hospital to home due to certain physical, psychological, social, and caregiving burdens, and in practice, patients' needs are not being met or are receiving transitional care services that are unequal and inconsistent with their actual needs, hindering their safe, healthy transition. The purpose of this study was to explore the perceptions of older adults and health care providers, including older adults, about the transition of care from hospital to home for older patients in one region of China. Objective To explore barriers and facilitators in the transition of care from hospital to home for older adults in China from the perspectives of older patients with chronic diseases and healthcare professionals. Methods This was a qualitative study based on a semi-structured approach. Participants were recruited from November 2021 to October 2022 from a tertiary and community hospital. Data were analyzed using thematic analysis. Results A total of 20 interviews were conducted with 10 patients and 9 medical caregivers, including two interviews with one patient. The older adult/adults patients included 4 men and 6 women with an age range of 63 to 89 years and a mean age of 74.3 ± 10.1 years. The medical caregivers included two general practitioners and seven nurses age range was 26 to 40 years with a mean age of 32.8 ± 4.6 years. Five themes were identified: (1) attitude and attributes; (2) better interpersonal relationships and communication between HCPs and patients; (3) improved Coordination of Healthcare Services Is Needed; (4) availability of resources and accessibility of services; and (5) policy and environment fit. These themes often serve as both barriers and facilitators to older adults' access to transitional care. Conclusions Given the fragmentation of the health care system and the complexity of care needs, patient and family-centered care should be implemented. Establish interconnected electronic information support systems; develop navigator roles; and develop competent organizational leaders and appropriate reforms to better support patient transitions.